2013
DOI: 10.4240/wjgs.v5.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary colon resection or Hartmann's procedure in malignant left-sided large bowel obstruction? The use of stents as a bridge to surgery

Abstract: There is still significant debate regarding the best surgical treatment for malignant left-sided large bowel obstruction. Primary resection and anastomosis offers the advantages of a definite procedure without need for further surgery. Its main disadvantages are related to the increased technical challenge and to the potential higher risk of anastomotic leakage that occurs in the emergency setting. Primary resection with end colostomy (Hartmann's procedure) is considered the safer option. Tan et al compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Endoscopic interventions are widely acknowledged as alternatives to surgery for colonic obstruction. A number of recent studies have established endoscopic stent placement as a valid primary or "bridging" therapy in the setting of malignant bowel obstruction (22)(23)(24)(25)(26). However, as evident in the present study, many patients with cancer are not appropriate candidates for endoscopic stent placement, and some who appear to be may not show any improvement after endoscopic intervention.…”
Section: Discussionmentioning
confidence: 41%
“…Endoscopic interventions are widely acknowledged as alternatives to surgery for colonic obstruction. A number of recent studies have established endoscopic stent placement as a valid primary or "bridging" therapy in the setting of malignant bowel obstruction (22)(23)(24)(25)(26). However, as evident in the present study, many patients with cancer are not appropriate candidates for endoscopic stent placement, and some who appear to be may not show any improvement after endoscopic intervention.…”
Section: Discussionmentioning
confidence: 41%
“…It is especially useful for debilitated patients who would not tolerate a midline laparotomy and for malignant disease that requires specialist expertise (that is not immediately available), further staging or neoadjuvant treatment. 2…”
Section: Discussionmentioning
confidence: 99%
“…Primary resection with an anastomosis offers the advantage of a definite procedure without the need for further surgery. However, the limitations of this procedure are the technical challenge and the potential risk of a high postoperative complication rate, depending on the general preoperative conditions or fecal-loading status of the colon [ 15 ]. The present study revealed that postoperative morbidity for left-colon OB patients who underwent a single-stage operation after on-table lavage did not significantly differ from that for NOB patients, despite the poor preoperative condition of the patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%